Patterns of Perpetration and Perceptions of Teen Dating Violence - Borges,Jeane Lessinger (2020)
Abstract This study investigated patterns of perpetration and perceptions of teen dating violence (TDV) in a sample of 428 adolescents characterized as perpetrators (62.4% female, M=16.73 years of age, SD=1.20) from the metropolitan region of Porto Alegre, state of Rio Grande do Sul (RS), Brazil. There was also a comparison group of 132 non-perpetrators (51.5% female, M=16.54 years of age, SD=1.19). The research instruments were a sociodemographic questionnaire, 15 items about the perception of TDV and the Conflict in Adolescent Dating Relationships Inventory (CADRI). We found a rate of 76.43% for the perpetration of some type of TDV and the most frequent was verbal/emotional violence (91.1%). The data showed that adolescents (perpetrators and non-perpetrators) have difficulty recognizing abusive behaviors, legitimizing the use of violence in their romantic relationships. Considering dating violence is a predictor of adult marital violence, the need to raise awareness of the phenomenon and the possibility of preventing TDV is discussed in this study.